(untitled) (AYUSHDHARA, 2024)
Ayurveda, encompasses eight branches known as Ashtangas. Among these, Shalakya Tantra specializes in the diagnosis and treatment of diseases affecting the Urdhwajatru-head and neck. Acharya Sushruta, a revered figure in Ayurvedic medicine, meticulously detailed the management of eleven head diseases, termed Shirorogas, in the Uttara Tantra of Sushruta samhita. One of these diseases, Kaphaja Shiroroga, closely aligns with the modern medical condition of Sinusitis based on its signs and symptoms. Kaphaja Shiroroga presents with symptoms such as a sensation of heaviness, mucus accumulation, stiffness, coldness and swelling around the eyes. Sinusitis, a contemporary counterpart, involves inflammation of the sinus tissues- air-filled spaces in the forehead, cheeks and nose. This inflammation results in facial pain, nasal congestion or discharge and sometimes fever, often triggered by a common cold. However, sinusitis can also be caused by viruses, bacteria, fungi, or allergies. Classified as a Kaphaja Vyadhi (disease caused by an imbalance of the Kapha dosha), Kaphaja Shiroroga is treated through various Ayurvedic procedures, including Shirovirechana (cleansing of head), Kavala (gargling), Snehana (oiling), Swedana (sudation), Vamana (therapeutic emesis), Upanaha (poultice) and Dhumapana (medicated smoking). The choice of treatment is determined by the physician’s expertise and tailored to the patient’s specific needs. By following these methodologies, Ayurveda aims not only to eradicate the disease but also to minimize the likelihood of recurrence, thus promoting long-term health and well-being.